VD_FINDINFO HC / 2014 / 580 vom 2. Mai 2014 - VD Tribunal cantonal (2014)
DÉLAI ABSOLU, PRESCRIPTION, DÉLAI RELATIF, INTERRUPTION DU DÉLAI, ACTION PÉNALE, LEX MITIOR | 60 al. 2 CO, 60 CO, 70a CP, 83 al. 1 LCR